Natural viral co‐infections in pig herds affect hepatitis E virus (HEV) infection dynamics and increase the risk of contaminated livers at slaughter. Issue 5 (22nd May 2019) - Salines, Morgane; Dumarest, Marine; Andraud, Mathieu; Mahé, Sophie; Barnaud, Elodie; Cineux, Maelan; Eveno, Eric; Eono, Florent; Dorenlor, Virginie; Grasland, Béatrice; Bourry, Olivier; Pavio, Nicole; et al.
Abstract: Hepatitis E virus (HEV) is a zoonotic pathogen, in particular genotype 3 HEV is mainly transmitted to humans through the consumption of contaminated pork products. This study aimed at describing HEV infection patterns in pig farms and at assessing the impact of immunomodulating co‐infections namely Porcine Reproductive and Respiratory Syndrome Virus (PRRSV) and Porcine Circovirus Type 2 (PCV2), as well as other individual factors such as piglets' immunity and litters' characteristics on HEV dynamics. A longitudinal follow‐up was conducted in three farrow‐to‐finish farms known to be HEV infected. Overall, 360 piglets were individually monitored from birth to slaughter with regular blood and faecal sampling as well as blood and liver samples collected at slaughterhouse. Virological and serological analyses were performed to detect HEV, PCV2 and PRRSV genome and antibodies. The links between 12 explanatory variables and four outcomes describing HEV dynamics were assessed using cox‐proportional hazard models and logistic regression. HEV infection dynamics was found highly variable between farms and in a lower magnitude between batches. HEV positive livers were more likely related to short time‐intervals between HEV infection and slaughter time (<40 days, OR = 4.1 [3.7–4.5]). In addition to an influence of piglets' sex and sows' parity, the sequence of co‐infections was strongly associated with different HEV dynamics: a PRRSV or PCV2/PRRSV pre‐ or co‐infection was associated with a higher age at HEV shedding (Hazard Ratio = 0.3 [0.2–0.5]), as well as a higher age at HEV seroconversion (HR = 0.5 [0.3–0.9] and HR = 0.4 [0.2–0.7] respectively). A PCV2/PRRSV pre‐ or co‐infection was associated with a longer duration of shedding (HR = 0.5 [0.3–0.8]). Consequently, a PRRSV or PCV2/PRRSV pre‐ or co‐infection was strongly associated with a higher risk of having positive livers at slaughter (OR = 4.1 [1.9–8.9] and OR = 6.5 [3.2–13.2] respectively). In conclusion, co‐infections with immunomodulating viruses were found to affect HEV dynamics in the farrow‐to‐finish pig farms that were followed in this study.